KERUKUNAN ANTARUMAT BERAGAMA SEBAGAI DASAR CITY BRANDING HARMONI KEDIRI THE SERVICE CITY - Irawan Hadi Wiranata; Marzuki Marzuki (Universitas Negeri Malang, 2018)
This article described inter-religious harmony as social identities of Kediri and the imple- mentation of Harmoni Kediri city branding as The Service City. This article used a qualitative de- scriptive approach with the form of case studies. Data collection used interview, observation and documentation techniques. The results of this study showed that inter-religious harmony was well established, due to the communication of religious leaders and community leaders who were mem- bers of the FKUB to create safe, peaceful and peaceful situations and conditions. To realize Harmoni Kediri’s city branding as The Service City through 3 (three) programs, namely: Prodamas; Coffee Tofu; and Heaven.DOI: http://dx.doi.org/10.17977/um019v3i12018p064